2016
DOI: 10.1016/j.numecd.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat intake modifies the influence of the FTO rs9939609 polymorphism on adiposity in adolescents: The HELENA cross-sectional study

Abstract: These findings support the concept that the deleterious effect of the FTOrs9939609 polymorphism on adiposity is exacerbated in adolescents consuming high fat diets. In contrast, the consumption of low fat diets (<30% of energy) may attenuate the genetic predisposition to obesity in risk allele carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
1
15
0
3
Order By: Relevance
“…A mechanistic explanation for the positive response of carriers of the FTO risk allele to behavioral modification is not clear, yet may be related to greater reduction of the brain's reward activation to food as a response to weight loss . In addition, it has been demonstrated that an FTO gene‐environment interaction in subjects who are physically active and/or have a low intake of fat results in a marked reduction of the obesogenic effect of the FTO AA gene variant . As both reduced fat intake and increased physical activity are central parts in most behavioral interventions, it is possible that in individuals with obesity, partly because of FTO, response is better to such interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanistic explanation for the positive response of carriers of the FTO risk allele to behavioral modification is not clear, yet may be related to greater reduction of the brain's reward activation to food as a response to weight loss . In addition, it has been demonstrated that an FTO gene‐environment interaction in subjects who are physically active and/or have a low intake of fat results in a marked reduction of the obesogenic effect of the FTO AA gene variant . As both reduced fat intake and increased physical activity are central parts in most behavioral interventions, it is possible that in individuals with obesity, partly because of FTO, response is better to such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, it has been demonstrated that an FTO gene-environment interaction in subjects who are physically active and/or have a low intake of fat results in a marked reduction of the obesogenic effect of the FTO AA gene variant. 36 As both reduced fat intake and increased physical activity are central parts in most behavioral interventions, it is possible that in individuals with obesity, partly because of FTO, response is better to such interventions. Hence, in the long-term, FTO genetic predisposition to obesity may result in a cycle of weight loss and regain.…”
Section: Discussionmentioning
confidence: 99%
“…Cecil et al [23] observed that children with the A allele have a preference for energy-dense food. In contrast, Labayen et al [24] showed that the FTO rs9939609 was not significantly associated with energy intake, but rather with the effect of the A allele on adiposity, which increased proportionally to the dietary fat content.…”
Section: Discussionmentioning
confidence: 88%
“…Fat intake may modifiy the effect of the FTO rs9939609 polymorphism on adiposity. It was observed that carriers of the A risk allele FTO rs9939609 had no significant influence on adiposity in subjects whose dietary fat intake was below 30% of total energy but fat intake higher than 30% increased central and total adipose tissues (20).…”
Section: Discussionmentioning
confidence: 99%